2016
DOI: 10.1161/circulationaha.115.020975
|View full text |Cite
|
Sign up to set email alerts
|

Right and Left Ventricular Function and Mass in Male Elite Master Athletes

Abstract: Background— It is under debate whether the cumulative effects of intensive endurance exercise induce chronic cardiac damage, mainly involving the right heart. The aim of this study was to examine the cardiac structure and function in long-term elite master endurance athletes with special focus on the right ventricle by contrast-enhanced cardiovascular magnetic resonance. Methods and Results— Thirty-three healthy white competitive elite ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(37 citation statements)
references
References 35 publications
4
31
1
1
Order By: Relevance
“…11 In contrast, Franzen et al demonstrated that LGE was absent in 20 men triathletes and 20 men middle-aged marathon runners. 32 Similarly, in a recent study of 33 elite male athletes and matched control subjects, with a median age of 47 years, only 1 athlete had LGE ‘localized subepicardial in the LV posteroinferior region.’ 33 The present study extends these findings by demonstrating a lack of association of focal myocardial necrosis across a significantly older population with longer physical activity histories and encompassing a spectrum of lifelong physical activity histories.…”
Section: Discussionsupporting
confidence: 72%
“…11 In contrast, Franzen et al demonstrated that LGE was absent in 20 men triathletes and 20 men middle-aged marathon runners. 32 Similarly, in a recent study of 33 elite male athletes and matched control subjects, with a median age of 47 years, only 1 athlete had LGE ‘localized subepicardial in the LV posteroinferior region.’ 33 The present study extends these findings by demonstrating a lack of association of focal myocardial necrosis across a significantly older population with longer physical activity histories and encompassing a spectrum of lifelong physical activity histories.…”
Section: Discussionsupporting
confidence: 72%
“…In elite athletes, the right ventricular end‐diastolic volume is increased compared with the LV end‐diastolic volume, and a bulge is noted on the RV free wall. Neither of these findings were seen in normal controls . As a result, a complete evaluation of the RV also needs to take into consideration outside factors other than just inherent contractility.…”
Section: Function Of the Rvmentioning
confidence: 97%
“…Neither of these findings were seen in normal controls. 5 As a result, a complete evaluation of the RV also needs to take into consideration outside factors other than just inherent contractility.…”
Section: Function Of the Rvmentioning
confidence: 99%
“…The subjects were studied by cardiopulmonary exercise test, 2D, TDI and Strain echocardiography to assess LV and RV morphology and function, and by contrast enhanced cardiac magnetic resonance. In the final results, although the athletes showed LV and RV enlargement in presence of normal biventricular function, a pathological late enhancement was detected in only one athlete, confirming how LV and RV dilation represents physiological remodeling and is not associated with ventricular dysfunction or risk of arrhythmias (Bohm et al, 2016). The contradictory results of published studies are principally due to the fact that neither the type of athletes (kind of sports, training history, period of evaluation) studied nor the methods used were homogenous, in particular for the differences in strain software analysis.…”
Section: Discussionmentioning
confidence: 63%